2010
DOI: 10.1002/adem.200980021
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Multi‐Wall Carbon Nanotubes for Lipase Immobilization

Abstract: We examine the immobilization of lipase B from Candida antarctica on functionalized multi‐wall carbon nanotubes (MWCNTs) through physical adsorption. MWCNTs functionalized with carboxyl‐, amine‐ and ester‐ terminal groups on their surface are used as immobilization carriers. Dispersion of the nanotubes and the immobilization procedure take place in aqueous and low‐water media. High enzyme loadings are attained, up to 25% of the weight of the carbon nanotubes. These novel biomaterials are characterized though F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 19 publications
(11 reference statements)
6
82
0
2
Order By: Relevance
“…This enzyme loading value is particularly high compared to the published values for other types of carbon-based nanomaterials (Asuri et al, 2007;Cang-Rong and Pastorin, 2009;Karajanagi et al, 2004). In previous work, we have shown that the immobilization yield could be improved by using a lower enzyme to nanomaterial weight ratio, albeit at the expense of the enzyme loading (Pavlidis et al, 2010a). The high immobilization yield observed for both immobilization procedures may also result from the adsorption of enzyme molecules on top of those previously immobilized (covalently or non-covalently) on the support, in a similar manner as described for other type of nanomaterials (Tzialla et al, 2010).…”
Section: Hydrolase Immobilization On Carbon-based Nanomaterialsmentioning
confidence: 79%
See 3 more Smart Citations
“…This enzyme loading value is particularly high compared to the published values for other types of carbon-based nanomaterials (Asuri et al, 2007;Cang-Rong and Pastorin, 2009;Karajanagi et al, 2004). In previous work, we have shown that the immobilization yield could be improved by using a lower enzyme to nanomaterial weight ratio, albeit at the expense of the enzyme loading (Pavlidis et al, 2010a). The high immobilization yield observed for both immobilization procedures may also result from the adsorption of enzyme molecules on top of those previously immobilized (covalently or non-covalently) on the support, in a similar manner as described for other type of nanomaterials (Tzialla et al, 2010).…”
Section: Hydrolase Immobilization On Carbon-based Nanomaterialsmentioning
confidence: 79%
“…The nanomaterials used in our study were functionalized with hexamethylenediamine, according to the procedure described in previous works (Bourlinos et al, 2003;Pavlidis et al, 2010a).…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, different nanoscale supports have been found to reduce diffusion limitations, enhance biocatalytic efficiency, and increasing the enzyme loading given the superior surface area per mass unit. Nanomaterials are wisely designed to enable long-term storage and recycling stability of the immobilized biocatalyst, while their unique physical and chemical properties create a favorable microenvironment for optimal enzymatic efficiencies [16,17].…”
Section: Fabrication Of Enzymatic Microreactorsmentioning
confidence: 99%